Pengaruh Penyajian dan Aksesibilitias Laporan Keuangan Daerah terhadap Akuntabilitas Pengelolaan Keuangan Daerah - Senda Yunita Leatemia; Paul Usmany (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2021)
The purpose of this study is to empirically examine the effect of the presentation and accessibility of regional financial reports on the accountability of regional financial management. This research is a quantitative research with several hypothesis testing. A sample of 87 respondents consisting of heads of offices, secretaries, heads of divisions, heads of sections and staff from each OPD of the Ambon City Government, who are involved in the process of managing regional finances. Based on the t test, it shows that the presentation of regional financial reports has a positive and significant effect on the accountability of regional financial management, while the accessibility of regional financial reports has no effect on the accountability of regional financial management. This is because regional financial reports have not been published openly through the mass media and information on regional financial reports is difficult to access by external parties.